Salinity Stress in Wheat (Triticum aestivum L.) in the Changing Climate: Adaptation and Management Strategies - EL Sabagh, Ayman; Islam, Mohammad Sohidul; Skalicky, Milan; Ali Raza, Muhammad; Singh, Kulvir; Anwar Hossain, Mohammad; Hossain, Akbar; Mahboob, Wajid; Iqbal, Muhammad Aamir; Ratnasekera, Disna; Singhal, Rajesh Kumar; Ahmed, Sharif; et al. (Frontiers in Agronomy, 2021)
Wheat is one the most popular and widely utilized cereals in the world owing to its multiple uses however increasing soil and water salinity poses a serious threat of its production. Salinity stress significantly influences the growth and development of wheat leading to diminish yield and quality. Wheat plants utilize a range of physiological biochemical and molecular mechanisms to adapt under salinity stress at the cell, tissue as well as whole plant level to optimize growth and yield. Recently, various adaptation and management strategies have been developed to reduce the deleterious effects salinity stress to maximize production and quality The review emphasizes the deleterious effects of salinity stress on wheat yield and quality and the adaptation and mitigation strategies for the sustainable wheat production to ensure food security.